The general public's access and use of health information: a case study from Brazil - Silva-Jerez, Nelson Sebastian; Furnival, Ariadne Chloe Mary (Universidade Federal de São Carlos, 2014)
The aim of the research was to map how members of the general public in Brazil find, access, evaluate and use health information found on the internet. Method. A survey of structured questions was made available online using Limesurvey, the same instrument being used as a protocol for face-to-face structured interviews with members of the public randomly selected. Analysis. The collected data underwent statistical analysis, performing simple correlations with variables of age, gender and occupation. Adapting the monitoring tool developed by Niemelä et al., a score for the participants' degree of everyday health information literacy was generated based on the participants' own perceptions of how they carry out certain daily information tasks. Results. Although participants obtain health information from medical and/or scientific sources, overall they lack confidence in their own skills to retrieve information and assess its reliability. Perceived credibility of health information sources on the Internet was higher for scientific articles, although only a quarter of participants in fact use these. Many participants claim to have used, or would use, health information found on the Internet in the decision-making process, including to change doctors. Conclusions. There was an identified latent desire to use more reliable information - understood in this research as being that of scientific, peer-reviewed and open access origin - in everyday health issues. Participants' relatively low estimation of their health information literacy skills could be tackled with public programmes directly aimed at minimising this perceived lacuna.
Keywords: Health information; Health information literacy; Open access; Scientific literature